Institutional Support in Increasing Entrepreneurial Self-efficacy and Performance of Woman Entrepreneurs - Filda Khoirun Nikmah; Bagas Gumintang; Purwati Purwati; Rohmawan Adi Pratama (Kuras Institute, 2023)
Entrepreneurial self-efficacy is an important factor in influencing new businesses for the success of woman entrepreneurs. Entrepreneurial self-efficacy refers to individual beliefs about skills and abilities in running a business. This research aims to show how women entrepreneurs, policymakers, and institutions maintain new businesses and encourage women's participation or success in entrepreneurship. This type of research is quantitative. The sampling process was carried out using a random sampling technique. Authors are obtaining data using an online questionnaire with a Google form. The filling link was distributed to women business actors in the second week of August 2022. There were 235 respondents as MSME actors. The research results show that: 1) women manage 95 percent of MSME actors. 2) young people manage 96 respondents or 40.85%. From the study results, it can be concluded that: 1) women have many contributions and are driving the wheels of the economy. 2) Women in Indonesia start businesses at a young age to earn income, reduce unemployment and improve people's welfare.